Znaczenie wprowadzania art. 12 § 2 k.k. i art. 57b k.k. dla praktyki wymiaru sprawiedliwości - Kluza, Jan (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The article discussed the issue of changes made to the Penal Code regarding criminal liability for acts taken in short intervals. In art. 12 § 2 of the Penal Code the legislator introduced a new provision under which, if the conditions set out in it are met, the perpetrator of several offenses is liable as for a crime. There are significant doubts as to the correct application of these provisions and the resulting consequences. In the amendment of 2020, the legislator introduced art. 57b of the Penal Code, on the basis of which the court must impose a more severe penalty for a continuous act. The consequences of this change, however, are even more far-reaching, which will be presented in the article.
Keywords: continuous act; sequence of offences; sequence of petty offences; rules of punishment